2020
DOI: 10.3389/fgene.2020.571880
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a High-Density Genetic Map and Identification of Quantitative Trait Loci for Nitrite Tolerance in the Pacific White Shrimp (Litopenaeus vannamei)

Abstract: Nitrite is a major environmental toxin in aquaculture systems that disrupts multiple physiological functions in aquatic animals. Although nitrite tolerance in shrimp is closely related to successful industrial production, few genetic studies of this trait are available. In this study, we constructed a high-density genetic map of Litopenaeus vannamei with 17,242 single nucleotide polymorphism markers spanning 6,828.06 centimorgans (cM), with an average distance of 0.4 cM between adjacent markers on 44 linkage g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 74 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…As example of the appli- Molecular markers based on single nucleotide polymorphisms (SNPs) have been recently implemented for selecting for growth performance, 113,114 resistance to V. parahaemolyticus in P. vannamei, 111,115 parvovirus in P. mergulensis 116 or even different stressors such as nitrite concentration. 117 Recently, Pooljun et al 118 have found an association between a SNP in the anti-lipopolysaccharide factor 3 (ALF3) and resistance to WSSV in P. monodon. These results open a new way to fight against the different diseases that threaten the industry with massive pathogenic outbreaks.…”
Section: Future Per S Pec Tive S and Con Clus Ionsmentioning
confidence: 99%
“…As example of the appli- Molecular markers based on single nucleotide polymorphisms (SNPs) have been recently implemented for selecting for growth performance, 113,114 resistance to V. parahaemolyticus in P. vannamei, 111,115 parvovirus in P. mergulensis 116 or even different stressors such as nitrite concentration. 117 Recently, Pooljun et al 118 have found an association between a SNP in the anti-lipopolysaccharide factor 3 (ALF3) and resistance to WSSV in P. monodon. These results open a new way to fight against the different diseases that threaten the industry with massive pathogenic outbreaks.…”
Section: Future Per S Pec Tive S and Con Clus Ionsmentioning
confidence: 99%
“…High-density genetic maps are essential and helpful for genome assembly at higher levels, comparative genomic analysis, and fine mapping of complex traits. To date, with the rapid development and application of high-throughput sequencing technology, high-density genetic maps of aquatic shrimps, including Litopenaeus vannamei ( Peng et al, 2020 ; Yu et al, 2015 ; Zhang et al, 2007 ), Penaeus monodon ( Guo et al, 2019 ; Wilson et al, 2002 ), and Fenneropenaeus chinensis ( Li et al, 2006 ; Wang et al, 2012 ), have been completed for reduced-representation genome sequencing. Based on this, the genetic mechanisms underlying sex determination have also been explored.…”
Section: Introductionmentioning
confidence: 99%